Preliminary Experimental and Numerical Study of the Tensile Behavior of a Composite Based on Sycamore Bark Fibers - Khoury Moussa, Helena; Lestriez, Philippe; Bui, He Thong; Nguyen, Pham The Nhan; Michaud, Philippe; Lucas-Roper, Romain; Antou, Guy; Luong, Viet Dung; Duong, Pham Tuong Minh; Abbès, Fazilay; Abbès, Boussad (Journal of Composites Science, 2024)
In the context of global sustainable development, using natural fibers as reinforcement for composites have become increasingly attractive due to their lightweight, abundant availability, renewability, and comparable specific properties to conventional fibers. This paper investigates the tensile properties of a sycamore bark fiber-reinforced composite. The tensile tests using digital image correlation showed that, by adding 18% by volume of sycamore bark for the polyester matrix, the tensile modulus achieves 4788.4 ± 940.1 MPa. Moreover, the tensile strength of the polyester resin increased by approximately 90% when reinforced with sycamore bark fiber, achieving a tensile strength of 64.5 ± 13.4 MPa. These mechanical properties are determined by the way loads are transferred between the polyester matrix and fibers and by the strength of the bond between the fiber-matrix interfaces. Since it is difficult and time consuming to characterize the mechanical properties of natural fibers, an alternative approach was proposed in this study. The method consists of the identification of the fiber elastic modulus using a finite element analysis approach, based on tensile tests conducted on the sycamore bark fiber-reinforced composites. The model correctly describes the overall composite behavior, a good agreement is found between the experimental, and the finite element predicted stress–strain curves. The identified sycamore bark fiber elastic modulus is 17,763 ± 6051 MPa. These results show that sycamore bark fibers can be used as reinforcements to produce composite materials.
Number: 9
Keywords: composite material; finite element analysis; mechanical properties; natural fiber; sycamore bark fiber